السماع والقياس في حمل اللفظ معنى آخر - Yuslina Mohamed; Wan Azura Wan Ahmad; Zainal Abidin Hajib; Mikail Ibrahim (Arabic Education Department, Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Non-Indexed Publication